Lectotypification of two Eriocaulon species (Eriocaulaceae) from India - Darshetkar, Ashwini M.; Datar, Mandar N.; Tamhankar, Shubhada; Choudhary, Ritesh Kumar (Phytotaxa, 2018)
Eriocaulon Linnaeus (1753: 87) is the largest genus of the family Eriocaulaceae Martinov (1820: 237). It is distributed in tropical and subtropical regions of the world and represented by ca. 471 species (Govaerts 2018). Ansari & Balakrishnan (2009) recorded 85 species of the genus from India. Lately, several new species have been published and the genus is now represented by 103 species in India (Darshetkar et al. 2017, Anto & Reshma 2017, Manudev et al. 2017, Naveen Kumar et al. 2017). Also, a few species of the genus have been lectotypified in last few years (Tiwari et al. 2016, Souladeth et al. 2017).